Dispersible SnO2:Sb and TiO2 Nanocrystals After Calcination at High Temperature. Issue 10 (17th January 2023) - Klein, Jonas; Philippi, Michael; Alarslan, Fatih; Jähnichen, Tim; Enke, Dirk; Steinhart, Martin; Haase, Markus
Abstract: High‐temperature treatment of functional nanomaterials, through postsynthesis calcination, often represents an important step to unlock their full potential. However, such calcination steps usually severely limit the preparation of colloidal solutions of the nanoparticles due to the formation of sintered agglomerates. Herein, a simple route is reported to obtain colloidal solutions of calcined n ‐conductive antimony doped tin oxide (ATO) as well as titanium dioxide (TiO2 ) nanoparticles without the need for additional sacrificial materials. This is achieved by making use of the reduced contact between individual nanoparticles when they are assembled into aerogels. Following the calcination of the aerogels at 500 °C, redispersion of the nanoparticles into stable colloidal solutions with various solvents can be achieved. Although a slight degree of sintering is inevitable, the size of the resulting aggregates in solution is still remarkably small with values below 30 nm. Abstract : Calcination at high temperatures is often required to achieve the full functionality of nanomaterials, but frequently prevents their redispersibility. However, formation of a nanoparticle aerogel prior to calcination retains the redispersibility as shown for two examples: Nanocrystals of antimony‐doped tin dioxide, where the full intensity of the plasmon absorption is reached only after calcination at 500 °C, and TiO2 nanoparticles.